Research Progress of β-Ketoenamine-Linked Covalent Organic Frameworks for Photocatalytic Hydrogen Evolution - Xue, Ping; Li, Mingyuan; Tang, Mi; Wang, Zhengbang; Wang, Chengliang (Organic Materials, 2024)
β-Ketoamide covalent organic frameworks (COFs), also named Tp-COFs, are considered to be a milestone material in the history of photocatalysts because of their excellent visible-light absorption, high crystallinity, ultra-high stability and structural diversity. In recent years, a large number of Tp-COFs and their composites have been successfully constructed based on molecular or composite engineering strategies, and exhibited splendid photocatalytic water splitting activity. In comparison with a composite strategy, the molecular engineering technique effectively avoids interface problems by designing and preparing frameworks at the molecular level. Therefore, it is necessary to timely summarize the construction of Tp-COF photocatalysts based on the molecular engineering strategy, so as to provide some theoretical basis and enlightenment for the subsequent development of high-performance Tp-COFs. Finally, the shortcomings and challenges of this technique and personal views on the further development of Tp-COFs are presented.
Keywords: β-ketoenamine; covalent organic frameworks; photocatalytic; hydrogen